In Search of Workers' Real Effort Reciprocity - A Field and a Laboratory Experiment - Heike Hennig-Schmidt; Bettina Rockenbach; Abdolkarim Sadrieh (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
updated version of paper no 55
urn:nbn:de:bvb:19-epub-13314-3
Keywords: C91; C92; J41; 330; efficiency wage; reciprocity; fairness; field experiment; real effort